A tree ring-based record of annual mass balance changes for the TS.Tuyuksuyskiy Glacier and its linkages to climate change in the Tianshan Mountains. (1st February 2019) - Zhang, Ruibo; Wei, Wenshou; Shang, Huaming; Yu, Shulong; Gou, Xiaohua; Qin, Li; Bolatov, Kainar; Mambetov, Bulkajyr T.
Abstract: Fluctuations in glacier mass and volume are indicative of changes in the climate system. They also strongly affect regional climate and hydrology. In this paper, we explore possible relationships between the radial growth of Schrenk spruce ( Picea schren kiana Fisch. et Mey) and the mass balance of the Tsentralniy Tuyuksuyskiy (TS. Tuyuksuyskiy) Glacier, which is located on the northern slopes of the Tianshan Mountains in arid central Asia. We attempt to reconstruct the historical mass balance variability of the TS. Tuyuksuyskiy glacier using tree-ring widths and stable carbon isotope chronologies. The reconstruction is able to explain 62.1% of the variance in the annual glacier mass balance record over the 1965–2014 calibration period. We also analyzed centennial mass balance variability and its linkages to climate change. The TS.Tuyuksuyskiy glacier has a negative annual mass balance in most years and, since 1968, has undergone the most rapid and longest melting process in the past 166 years. The mass balance change of the glacier is controlled by the combination of temperature and precipitation conditions. This study could be useful for more detailed glaciological, hydrological, and climatological assessments in this portion of the Tianshan Mountains. Highlights: The reconstruction of glacial changes using tree ring widths and stable carbon isotopes is reliable in arid central Asia. The TS.Tuyuksuyskiy glacier has had a negative annual mass balance for most of the past 166 years. The mass balance change of the glacier is controlled by the combination of temperature and precipitation.